O odrodzenie wychowania = For the resurrection of education - Wielgus, Stanisław (1939- ) (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The author's own vision of education is derfted in the context of contemporary cultural and educational situation of the young generation and declares that the intensification of educational activities and augmentation of financial support alone will not be able to solve the existent crisis in education. The problem calls for the transformation of educational objectives as well as for the redefiniti on of methods by which they have been pur into practice. lt also demands a transformation of teachers themselves. The author indicates the possible procedures for solving the problems.
Keywords: wychowanie